Advanced Measuring (Instrumentation) Methods for Nuclear Installations: A Review. (20th September 2012) - Qiu-kuan, Wang; Chang-hua, Lin; Yan, Yang
Abstract : The nuclear technology has been widely used in the world. The research of measurement in nuclear installations involves many aspects, such as nuclear reactors, nuclear fuel cycle, safety and security, nuclear accident, after action, analysis, and environmental applications. In last decades, many advanced measuring devices and techniques have been widely applied in nuclear installations. This paper mainly introduces the development of the measuring (instrumentation) methods for nuclear installations and the applications of these instruments and methods.